Effect of intermittent hypoxic training on 20 km time trial and 30 s anaerobic performance - Hamlin, M. J.; Marshall, H. C.; Hellemans, J.; Ainslie, P. N.; Anglem, N. (Scandinavian Journal of Medicine & Science in Sports, 2010)
This study aimed to verify whether the "live low, train high" approach is beneficial for endurance and/or anaerobic cycling performance. Sixteen well-trained athletes completed 90 min of endurance training (60-70% of heart rate reserve), followed by two 30-s all-out sprints (Wingate test), daily, for 10 consecutive days. Nine subjects [intermittent hypoxic training (IHT) group] trained with an FIO2 set to produce arterial oxygen saturations of appr. 88-82%, while seven subjects (placebo group) trained while breathing a normal gas mixture (FIO2=0.21). Four performance tests were conducted at sea level including a familiarization and baseline trial, followed by repeat trials at 2 and 9 days post-intervention. Relative to the placebo group, the mean power during the 30-s Wingate test increased by 3.0% (95% confidence limits, CL ± 3.5%) 2 days, and 1.7% (± 3.8%) 9 days post-IHT. Changes in other performance variables (30 s peak power, 20 km mean power and 20 km oxygen cost) were unclear. During the time trial, the IHT participants' blood lactate concentration, respiratory exchange ratio, and SpO2, relative to the placebo group, was substantially increased at 2 days post-intervention. The addition of IHT to the normal training program of well-trained athletes produced worthwhile gains in 30 s sprint performance possibly through enhanced glycolysis.